The huntress : [compact disc, unabridged] a novel - Quinn, Kate (Harper Audio, 2019)
Bold and fearless, Nina Markova always dreamed of flying. When the Nazis attack the Soviet Union, she risks everything to join the legendary Night Witches, an all-female night bomber regiment wreaking havoc on the invading Germans. When she is stranded behind enemy lines, Nina becomes the prey of a lethal Nazi murderess known as the Huntress, and only Nina's bravery and cunning will keep her alive.